The organization and evolution of dorsal stream multisensory motor pathways in primates - Jon H Kaas; Omar eGharbawie; Iwona eStepniewska (Frontiers Media S.A., 2011)
In Prosiman primates, New World monkeys, and Old World monkeys microstimulation with half second trains of electrical pulses identifies separate zones in posterior parietal cortex (PPC) where reaching, defensive, grasping, and other complex movements can be evoked. Each functional zone receives a different pattern of visual and somatosensory inputs, and projects preferentially to functionally matched parts of motor and premotor cortex. As PPC is a relatively small portion of cortex in most mammals, including the close relatives of primates, we suggest that a larger, more significant PPC emerged with the first primates as a region where several ethologically relevant behaviors could be initiated by sensory and intrinsic signals, and mediated via connections with premotor and motor cortex. While several classes of PPC modules appear to be retained by all primates, elaboration and differentiation of these modules likely occurred in some primates, especially humans.